The end of print media? - Benni Setiawan (Universitas Negeri Yogyakarta, 2022)
The publication end of print media certainly remains some serious problems. First, the termination of employment for media workers. The layoff may target the workers who operate machines and or workers at the circulation section. The publication end of Republika print media has caused more than 200 people out of work. Of course, this is not a small number. In fact, the laid-off workers should hold and fulfill their family life needs. This means that there will be an extraordinary upheaval for media workers when the print newspaper edition closes. Second, the end of newspaper print editions causes many newspaper peddlers/sellers to be unemployed. This is a very sorry situation as they belong to low-income people who must lose their job. Their income is highly dependent on how many copies of the newspaper are sold. The sales of print newspapers are not profitable. When fewer print newspapers are in circulation and the people purchasing power is small, the more painful the life of newspaper sellers will be.